Putting the "Strategic" into Strategic Religious Engagement. (1st November 2021) - Wilkinson, Olivia
Abstract : In light of the lessons learned both from COVID-19 response and now over 20 years of research on religious engagement, this essay lays out the flaws in current religious engagement in humanitarian and development work. Religious engagement can be seen as unknown, unevidenced, and unacknowledged by development agencies. Now knowing more than ever about religious engagement, there are mistakes that can be avoided by understanding the previous religious engagements, challenging secular-religious dynamics, and purposefully using the evidence. Overall, the essay argues that current religious engagement is not strategic, but suggests how each of these flaws can be counteracted.